A Tracking Algorithm of Moving Target in Sports Video - Zhang Hai Tao (Institute of Advanced Engineering and Science, 2014)
Moving target tracking is a core subject in the field of computer vision, its core idea is comprehensive utilization of image processing, video analysis technology, quickly and accurately capture the moving targets. In order to obtain all kinds of technical parameters in the training of athletes, the traditional way is through various sensors used in the athletes. The shortcomings of this method is not put the influence of sensor techniques for athletes in consideration, so it is urgent to have a new technical means to get better movement parameters of the athletes, the traditional target tracking algorithm is difficult to achieve good results, in this study, based on the characteristics of sports video, and it makes some transform to the traditional tracking algorithm, and it proposes a new hybrid tracking algorithm. This algorithm not only can solve the difficult problems of sports video target tracking, and but also can reduce the complexity of the algorithm, through the related analysis and experiments in sports video software, the algorithm can achieve good effect.